Differential proteomics of interstitial fluid in lung tissue associated with the progression of pulmonary fibrosis in mice - Xi Lu; Dong Han; Yifeng Nie; Yahong Shi; Tun Yan; Xiang Li (Scientific Reports)
Abstract Idiopathic pulmonary fibrosis (IPF) is a chronic and fatal fibrosis disease. Due to the limited understanding of its pathogenesis and the fact that its detection largely depends on the operator’s technical level and the accuracy of the equipment, the diagnosis and treatment of the disease have significant limitations. In this research, bleomycin was used to establish IPF models of C57/BL6N mice with different injury degrees, and proteomics technology extracted interstitial fluid of lung tissue to analyze the mechanism of fibrosis at different stages. Compared with the normal group, the alveolar area, collagen deposition, tidal volume, and respiratory rate of the experimental group decreased at all periods, and the difference was most significant on the 14th day of modeling. Proteomic techniques, including gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, showed that the progression of pulmonary fibrosis was related to different pathways: glucose metabolism, lipid transport, glycoprotein metabolism, synthesis of sulfur compounds, and other energy metabolism, calcium ion transport were dominant in the early stage of fibrosis and the acute inflammatory stage. The endoplasmic reticulum stress pathway was dominant in the extreme stage of fibrosis, and blood flow shear stress, Extracellular matrix (ECM) receptor activation, and other extracellular matrix-related pathways were dominant in the late stage of fibrosis. Moreover, western bolt validation experiments also confirmed that C/EBP-homologous protein (CHOP), Heat Shock Protein 60 (HSP60), and Alpha smooth muscle actin(α-SMA) proteins were increased in expression related to this pathway at the extreme stage of fibrosis, suggesting that the disruption of ion balance in the endoplasmic reticulum induced by endoplasmic reticulum stress or the disturbance of protein processing and transportation were involved in the occurrence and development of pulmonary fibrosis in mice. The above results are expected to provide ideas for clinical interpretation of the mechanism of pulmonary fibrosis and provide vital data support for its accurate diagnosis and effective treatment.